SYSTEMATIC LITERATURE REVIEW: PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMK - Aslamiyah, Maulida; Nindiasari, Hepsi (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
This study aims to determine the influence of the problem-based learning model on the mathematical problem-solving ability of vocational school students. This study uses the SLR (Systematic Literature Review) method by reviewing as many as 20 articles from journal publications from January 2019 to March 2024. The data analysis techniques taken used the interaction model (Miles & Huberman), namely data collection, data reduction, data presentation, and conclusion. The application of the PBL (Problem Based Learning) model has a positive effect on the mathematical problem-solving ability of vocational school students, there is a better difference in the value of the experimental class that is treated with the PBL model compared to the control class that is treated with the conventional learning model, and is worth testing along with supporting learning media. Keywords: Problem Based Learning, Problem Solving Capabilities